PENGARUH PENDIDIKAN KESEHATAN MEDIA VIDEO ANIMASI TERHADAP PENGETAHUAN CUCI TANGAN PAKAI SABUN PADA ANAK USIA SEKOLAH - dewi pujiana; Selika Prahayu; Puji Setya Rini (IKesT Muhammadiyah Palembang, 2024)
ABSTRACT Introduction: Handwashing with soap is one of the sanitary measures by cleaning hands and fingers using water and soap. Washing hands using soap is an effort to prevent disease. In increasing knowledge of washing hands with soap by using animated video media. Objective: To determine the effect of health education animation video media on the knowledge of handwashing with soap in school-age children at SD Negeri X Palembang. Method: This research is a quantitative research with the method